1974
DOI: 10.1192/bjp.124.1.052
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Trial of Long-Term Lithium Therapy in Mental Defectives

Abstract: The therapeutic effect of lithium in mania was first described by Cade (1949), but the possibility that lithium could have a prophylactic action in recurrent affective disorders was not suggested until some years later (Hartigan, 1963; Baastrup, 1964). The early studies of the prophylactic action of lithium were open trials, in which both investigator and patient knew that the patient was receiving the drug. More recently, controlled double-blind studies have confirmed these early reports (Melia, 1970; Coppene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Fourteen studies or case reports were included in their analysis. Eight were descriptive studies [63][64][65][66][67][68][69][70], 2 investigated the efficacy of certain types of treatment [71,72], 3 combined description and treatment efficacy [73][74][75]) and 1 examined rating scales for mood disorders [76]. Methodologies were highly variable, numbers of patients per report were small (10 was the largest N) and outcome measures, if reported at all, were non-rigorous.…”
Section: Mood Stabilizers/anticonvulsantsmentioning
confidence: 99%
“…Fourteen studies or case reports were included in their analysis. Eight were descriptive studies [63][64][65][66][67][68][69][70], 2 investigated the efficacy of certain types of treatment [71,72], 3 combined description and treatment efficacy [73][74][75]) and 1 examined rating scales for mood disorders [76]. Methodologies were highly variable, numbers of patients per report were small (10 was the largest N) and outcome measures, if reported at all, were non-rigorous.…”
Section: Mood Stabilizers/anticonvulsantsmentioning
confidence: 99%
“…By way of validation, family histories often contained cognitively normal relatives with affective disorders, and some response to lithium was observed (Carlson, 1979;Hasan & Mooney, 1979;Naylor, Donald, Le Poidevin, & Reid, 1974;Reid, Naylor, & Kay, 1981;Sovner & Hurley, 1981), with or without neuroleptics. In some cases, response to lithium was miraculous.…”
Section: Lithiummentioning
confidence: 99%
“…In 1949, Cade introduced the use of lithium salts to quiet agitated manic states, however, it took 20 years before a technology was developed to manage lithium's toxicity. Naylor, Donald, Poidevin, and Reid, (1974) studied 14 patients over a 2-year-period and found that lithium was useful in the treatment of patients with dual diagnosis and frequently recurring affective changes or recurrent behavioral changes. Rivenus and Harmatz (1979) described a 3-year single-blind placebo-controlled trial of lithium in five institutionalized patients with ID and bipolar disorder.…”
Section: Bipolar Disordermentioning
confidence: 99%